Evaluation of in silico antidiabetic activity of phytocompounds of wild bitter gourd on DPP4 target - Em, Pham Canh; Trang, Nguyen Ly Doan; Thuong, Luong Thi; Ly, Nguyen Thuy Dan; Anh, Nguyen Thi Ngoc; Trung, Nguyen Quoc; Trinh, Nguyen Huynh My (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Wild bitter gourd (Momordica charantia var. abbreviata Ser.) shows diverse pharmacological effects, especially containing many phytocompounds with potential antidiabetic activity. Forty-one bioactive compounds were screened for antidiabetic activity through the inhibition of DPP4 (dipeptidyl peptidase 4) by molecular docking with AutoDock Vina software. Momordicoside T (-10.1 Kcal/mol), Momordicoside B (-9.9 Kcal/mol), Momordicoside F1 (-9.8 Kcal/mol), and Momordicoside I (-9.7 Kcal/mol) showed the strongest interaction with the DPP4 target compared to co-crystallized ligand and reference drug Vildagliptin (-6.9 Kcal/mol). These Momordicosides formed many strong hydrogen bonds at the DPP4 active site. In particular, Momordicoside T established the most hydrogen bonds with bond lengths ranging from 1.92-2.94 Å. The structure linked with sugar moieties increased the hydrogen bond formation and binding affinity of these phytocompounds with DPP4. Therefore, these compounds could be potential molecules to develop new antidiabetic drugs on DPP4.